KAJIAN STRUKTUR KOLONG DAN PERGESERAN FUNGSI GARDU POS RONDA STUDI KASUS PADA GARDU POS RONDA RW 29 MOJOSONGO, JEBRES, SURAKARTA - Sumarno, S., (Acintya, 2015)
Night watch guardhouse (gardu pos ronda) is one of Indonesian cultural uniqueness forms compared with other states remaining to exist up to now. In such the condition, guardhouse is also a witness of historical course from several eras accompanying. The uniqueness of guardhouse lies, among otherthings, at its form and the system accompanying it. The structure of guardhouse is as same as other architecture construction consisting of floor, wall and roof. Several guardhouses, by its floor structure, consist of kolong (space underneath main construction) floor and guardhouse exactly on the land. Amid the architectural culture abandoning kolong structure particularly in Java, the structure of guardhouse kolong is an interesting topic to study. It is because the kolong structure is the reflection of Javanese floor construction structure in the past. The objective of research is to find out: (a) what the structure of guardhouse construction is as the interior element; (b) in the present context, how the change of the development of guardhouse function is and what activities it serves in addition to guard security. In order to achieve the objective, the research method employed was a qualitative research.The research was taken place in Surakarta city. The sampling technique used was purposive sampling one taking all of guardhouses with kolong structure existing in RW 19, Kelurahan Mojosongo, Jebres Subdistrict, Surakarta City. Techniques of collecting data used include interview, recording, librarystudy, measurement, and documentation. The data validation is conducted using data triangulation, while the data analysis is done by using Miles and Huberman’s interactive model of analysis.Keywords: guardhouse, kolong structure, function.